Observational study of the type IIb supernovae 2017gkk and 2019gaf - Koivisto, Niilo (My University, 2022)
Supernova (SN) is bright explosion of a star at the end point of stellar evolution. Supernova explosions caused by gravitational collapse of the core of the star are called core-collapse supernovae (CCSNe), which can be classified to several types, such as II, Ib and Ibc, based on their spectral features. Type II shows strong hydrogen (H) features, type IIb shows weak H features and Ibc shows no H features. Strength of the features reflects the amount H in the envelope of their progenitors at explosion, which depends on their mass loss history. The progenitor stars of type Ibc SNe have lost their H envelope through mass loss, as for type II SNe H envelope of the SN progenitor are intact at explosion. Type IIb SNe are intermediate case of these types. The mechanism for the mass loss is unclear. In general, massive stars have two major mass loss processes: the stellar wind and the binary effects. Stars with higher mass and higher metallicity have stronger stellar winds, which suggest that these properties of the progenitor star should determine the type the SN explosion. In case that the mass loss is caused mainly by the binary effects, the mass loss would be affected by the binary parameters rather than the properties of the progenitor. This connection between the mass loss mechanism and the observational properties of SNe enables us to investigate the origin of SN progenitors. In this thesis, I used the photometric and spectroscopic observations on SNe 2017gkk and 2019gaf to study the properties of the progenitor stars and the SNe explosions. In particular, I derived the progenitor mass and explosion properties such as the ejecta mass, the ejecta velocity, the 56 Ni mass and the rise time for both SN. As a future work, I will compare these values to other type IIb SNe as well as other CCSNe, taken from the literature. These comparisons I will use to discuss the mass loss mechanism of the stripped envelope SN (SE SN) and the origin of the type IIb.
Keywords: Supernovae, Core-collapse supernovae, Type IIb SNe, SN 2017gkk, SN 2019gaf